2022
DOI: 10.5935/1518-0557.20220057
|View full text |Cite
|
Sign up to set email alerts
|

Impact of sperm DNA fragmentation on the clinical outcome of assisted reproduction techniques: a systematic review of the last five years

Abstract: Objective: To elucidate through a systematic literature review the impact sperm DNA fragmentation has on embryos from assisted reproduction techniques. Data Source: Studies from the "PubMed", "Embase", and "BVS" databases were analyzed. Studies Selection: The articles selected in the review included: cohort and case-control studies that addressed the proposed theme, published between January 1, 2017, and January 31, 2022, in English, Portuguese, and Spanish. As inclusion criteria: cohort and case-control artic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 50 publications
2
8
0
Order By: Relevance
“…Interestingly, when swim-up was the control method, the rates appeared more favorable for this group. This observation aligns with the notion that techniques preserving the acrosomal cap might cause less DNA damage to sperm [54,55], though this premise remains debated [56].…”
Section: Laboratory Outcomessupporting
confidence: 84%
See 1 more Smart Citation
“…Interestingly, when swim-up was the control method, the rates appeared more favorable for this group. This observation aligns with the notion that techniques preserving the acrosomal cap might cause less DNA damage to sperm [54,55], though this premise remains debated [56].…”
Section: Laboratory Outcomessupporting
confidence: 84%
“…For total blastocyst formation (Fig 4C ) and the derivation of good/excellent quality blastocysts (Fig 4D ), the data leaned in favor of MFSS usage. Though not achieving statistical significance, these findings buttress the argument for enhanced outcomes when spermatozoa avoid rigorous procedures during ICSI selection [54].…”
Section: Laboratory Outcomesmentioning
confidence: 74%
“…All studies showed that DNA fragmentation had a negative impact on embryo quality and development in IVF as well as ICSI cycles. 70 In agreement with these results, a recent retrospective study involving 176 couples with unexplained infertility undergoing IVF or ICSI showed that SDF levels >25% were significantly correlated with a decrease in the number of day 3 good-quality embryos ( r = −0.347, p < 0.001). 71 In contrast to these findings, previous systematic reviews that gathered evidence from numerous sources did not establish a clear association.…”
Section: Sperm Dna Fragmentation and Assisted Reproductive Technologysupporting
confidence: 63%
“…The technique used in laboratories that are considered the gold standard for attempting to diagnose male infertility is semen analysis. It evaluates the factors of infertility such as morphology, sperm motility, liquefaction time, seminal volume, sperm concentration, and sperm [ 5 ]. ART has been widely included in the management of infertile couples.…”
Section: Introductionmentioning
confidence: 99%